A Novel Numerical Approach for the Analysis of 2D MEMS-Based Variable Capacitors Including the Effect of Arbitrary Motions - Kuroda, Michiko; Miura, Noriyuki; Tentzeris, Manos M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A novel time-domain technique is proposed for the analysis of MEMS-based variable devices involving motion to arbitrary in-plane directions using the adaptive body fitted grid generation method with moving boundaries. MEMS technology is growing rapidly in the RF field and the accurate design of RF MEMS switches that can be used for phase shifting or reconfigurable tuners requires the computationally effective modeling of their transient and steady-state behavior including the accurate analysis of their time-dependent moving boundaries. Due to the limitations of the conventional time-domain numerical techniques, it is tedious to simulate these problems numerically. The new technique proposed in this paper is based on the time-difference time-domain method with an adaptive implementation of grid generation. Employing this transformation, it is possible to apply the grid generation technique to the analysis of geometries with time-changing boundary conditions. A variable capacitor that consists of two metal plates that can move to arbitrary in-plane directions is analyzed as a benchmark. The numerical results expressing the relationship between the velocity of the plates and the capacitance are shown and the transient effect is accurately modeled.